Nevirapine biotransformation insights - Cipriano, Madalena (2020)
Funding: This work was supported by FCT (Portugal) through the research grant PTDC/MED-TOX/29183/2017. Acknowledgments: The authors thank ECBio S.A. for providing the hnMSCs and F.A. Beland (NCTR, Jefferson, AR, USA) for the kind donation of nevirapine. FCT (UID/DTP/04138/2019, UID/QUI/00100/2019, RECI/QEQ-MED/0330/2012, SFRH/BD/144130/2019 to J.S.R., SFRH/BD/110945/2015 to P.F.P. and CEECIND/02001/2017 to A.M.M.A) are also acknowledged.